Are small or large producers driving the Canada‐U.S. labour productivity gap? Recent evidence from manufacturing. (May 2014) - Tang, Jianmin
Abstract This paper shows that the higher small‐plant employment share in Canada compared with the United States mattered for the Canada‐U.S. manufacturing labour‐productivity gap, but it did not contribute to the widening of the gap between 2002 and 2007. In addition, it shows that while the weaker productivity performance of small plants in Canada compared with the United States accounted for much of the gap in a particular year, the deterioration in the productivity performance of large plants in Canada was responsible for most of the widening gap over this period.